Bank Account Ownership and Access Among In-Patients in Psychiatric Care in Berlin, Germany—A Cross-Sectional Patient Survey - Schreiter, Stefanie; Bermpohl, Felix; Schouler-Ocak, Meryam; Krausz, Michael R.; Rössler, Wulf; Heinz, Andreas; Gutwinski, Stefan (Frontiers in Psychiatry, 2020)
Background: Access to a bank account is critical for overall participation in social life and an indicator for social integration. Worldwide about 1.7 billion people remain with no access to banking facilities as a form of financial exclusion which represents 31% of the world’s general population. In contrast, in Western countries like Germany, 99% of the general population use bank accounts. Methods: We conducted an exploratory cross-sectional survey on bank account ownership and bank account access among psychiatric in-patients in a psychiatric hospital in Berlin. Out of 540 participants who were reached for an interview, 486 shared information about bank account ownership and 469 on access. Results: Out of 486 participants 49 (10.1%) did not own a bank account. Among the remaining 420 participants owning a bank account, 36 (8.3%) did not have direct access to their bank account, but only e.g. their legal guardian. Regression results found psychosis, intellectual disabilities, a longer treatment duration as well as being of male gender and a more instable housing status to be significantly associated with a missing bank account or a missing access to one’s bank account. Conclusions: The lack of bank account ownership and access among this population of psychiatric patients is concerning.. The interrelationship between factors of financial exclusion and mental health should be further explored in longitudinal studies. More attention is needed to support people with severe mental illness to be able to access resources associated with financial inclusion.